Perancangan Prototipe Pembangkit Listrik Tenaga Gelombang Sungai Menggunakan Gerak Translasi Magnet Permanen - Sri Agustina; Antonius Hamdadi; Dwirina Yuniarti; Daniel Trivaldo Simatupang; Akbar Dwi Fortuna; Herlina Wahab (Fakultas Teknik Universitas Pancasila, 2022)
Fossil energy sources are becoming increasingly expensive and will be unable to meet future energy demands. To address the scarcity of fossil fuels, many researchers are turning their attention to renewable energy sources. These sources of energy include wind, solar, geothermal, ocean waves, and others. The area around South Sumatra is rich in rivers, so this study utilizes the waves of the Musi River as the driving force for the River Wave Power Plant (PLTGS). The mechanism of this PLTGS is a permanent magnet generator designed to utilize the waves of the Musi River as the driving input of the generator. The river waves will move the float above, which has been arranged vertically with several permanent magnets, which will cut the magnetic field from the stator coil. The generator is designed to move translationally according to wave motion. The movement of the magnet also occurs from the impulse of the water wave, which causes the magnet to approach the stator coil and produce an induced electromotive force on the generator. Six generators are used, with each generator containing four Neodymium magnets and 1500 coils. The respective induced voltages are stored temporarily in the capacitors of the generator. The entire generator is connected in series. From the calculation results, the calculation results of the induced emf multiplied by the coil and the number of turns is 18.17 volts. Meanwhile, from the direct measurement results, the average voltage that can be generated is 10.9 volts. There is a voltage difference of 7.24 volts between theoretical calculations and direct measurements. This difference is caused by losses in the tool, such as friction, air gaps, and cable length. A permanent magnet generator that moves with the waves of the river can be used to make electricity, according to the results of this study